Alterity, Otherness and Journalism: From Phenomenology to Narration of Modes of Existence - Freitas, Camila; Benetti, Marcia (Brazilian journalism research, 2017)
In a theoretical reflection, the aim of this paper is primarily to discuss alterity in journalism. We believe that journalism plays a fundamental role in the construction of knowledge on similarities and differences between human beings, stressing social diversity as one of its purposes. We associate the concept of otherness, understood as a singular mode of existence of the “other”, with the purpose of journalism and with actions of empathy, sympathy and compassion. Based on a phenomenological perspective, we discuss the importance of the meeting between the "self" and the "other", as well as the ability of journalists to perceive and narrate on the aspects that shape the identities of human beings. Moreover, we discuss otherness in journalistic narratives, approaching the relation between the lifeworld and the world of text, taking into consideration the elements of perception, mimesis, textuality and interpretation. Este artigo tem caráter teórico e visa discutir a alteridade no jornalismo. Consideramos que o jornalismo tem um papel fundamental na construção do conhecimento sobre as semelhanças e as diferenças entre os seres humanos, sendo a apresentação da diversidade social uma de suas finalidades. Propomos associar o conceito de outridade, compreendida como o modo de existência do “outro” em sua singularidade, a essa finalidade do jornalismo e a ações de empatia, simpatia e compaixão. Adotamos uma perspectiva fenomenológica, indicando a relevância da experiência do encontro entre o “eu” e o “outro” e a capacidade de o jornalista perceber e narrar os aspectos que configuram as múltiplas identidades dos seres. Tratamos ainda da outridade na narrativa jornalística, abordando a relação entre o mundo da vida e o mundo do texto e discutindo os princípios da percepção, da ação mimética, da textualidade e da interpretação. Este artículo de carácter teórico analiza la alteridad en el periodismo. Creemos que el periodismo tiene un papel fundamental en la construcción de los saberes acerca de las similitudes y diferencias entre los seres humanos, una vez que la presentación de la diversidad social és uno de sus propósitos. Combinamos el concepto de otredad, que se entiende como el modo de existencia del "otro" en su singularidad, con la finalidad del periodismo. Adoptamos un punto de vista fenomenológico, lo que indica la importancia de la experiencia del encuentro entre "yo" y "otro" y la capacidad del periodista para percibir y narrar características de las múltiples identidades de los seres. También trabajamos con la otredad en la narrativa periodista, presentando la relación entre el mundo de la vida y el mundo del texto, así tratando de los principios de la percepción, de la acción mimética, de la textualidad y de la interpretación.